Performance evaluation of a cold storage system using pure conduction simulation with nanomaterial integration - M. Saif Aldien; Ali Basem; Hussein A.Z. AL-bonsrulah; Adel Almarashi; Moaz Al-lehaibi; Nasrin B.M. Elbashir (Case Studies in Thermal Engineering)
This study emphasizes key progresses in cold storage system productivity achieved via the implementation of fins and porous foam. The analysis focused on radiation and conduction mechanisms, omitting the convective term due to the nature of the solidification process. The mathematical framework incorporated two coupled equations to ensure precise system modeling. Numerical methods combined with adaptive mesh refinement were employed for simulations. The system design featured a wavy outer wall and a circular inner wall fortified with fins. Validation tests demonstrated the model's accuracy and reliability. The inclusion of porous foam significantly accelerated freezing, reducing the process duration by approximately 90.73 % due to enhanced thermal conduction. Hybrid nanoparticles further boosted freezing efficiency by about 7.32 %. Moreover, an increased radiation factor led to a reduction in completion time by nearly 17.38 %.